THE INFLUENCE OF ELECTRONIC GOVERNMENT ON THE QUALITY OF SERVICES OF BADUNG REGENCY DRINKING WATER REGIONAL COMPANIES - I Putu Dharmanu Yudartha; Ni Wayan Supriliyani (West Science Interdisciplinary Studies, 2023)
This study aims to analyze the influence of electronic government in improving service quality for PDAM Tirta Mangutama customers. The method in this study uses the quantitative method, which is to analyze the effect of e-government on service quality. Associative quantitative data analysis asks about the relationship between two or more variables. The normality test results show that it is normally distributed through the Kolmogorov-Smirnov Test. Then based on the linearity test shows a value of 0.95, which means greater than the sig value of 0.05. It means that there is a relationship between these two variables. The heteroscedasticity test shows that the sig value is 0.695, greater than 0.05, so heteroscedasticity does not occur. A simple regression analysis with an R square value of 0.355 or an effect of 35.5 percent and an R-value of 0.596 means it is in the medium category. The T-Test and F-test show that Ha is accepted, meaning that e-government influences the quality of public services in the Regional Drinking Water Company of Tirta Mangutama, Badung Regency.